CHARACTERIZATION OF HYDROTHERMAL ALTERATION ZONES IN PANTI GEOTHERMAL FIELD, PASAMAN DISTRICT, WEST SUMATERA PROVINCE - Supriadi, Wildani; Haryanto, Agus Didit; Hutabarat, Johanes; Simarmata, Robertus S. L.; Asoka, Widya (Journal of Geological Sciences and Applied Geology, 2018)
anti geothermal area is located in Pasaman Regency, West Sumatra Province. The survey areais about 200 km away from the city of Padang and about 30 km away from the capital city ofPasaman Regency, Lubuk Sikaping. The purpose of this research activity was to determine thecharacteristics of hydrothermal alteration in an observed well. The method used was petrologicalanalysis on PNT-1 well core data from the depth of 41.5 m until 533.5 m, petrography analysis of17 rock samples, and Specterra analysis based on secondary data. The alteration minerals thatappeared in the observed well were calcite, sericite, chlorite, secondary quartz, anhydrite,opaque minerals, iron oxide, clay, and epidote minerals; with alteration types in the form ofreplacement and direct depositional. Two zones were sorted based on the presence of mineralsand determination of alteration zones, namely the Smectite-Chlorite zone, and the illit-smectitechloriteand sericite zone. The smectite-chlorite zone was located at thedepthof±41-±454mandwascharacterizedbythepresenceofsmectite,ilite-smectite,calcite,andchloritealterationminerals;whichweremoredominantthanotheralterationminerals.Thiszoneaccordingtothealterationzone division comprised of argillic zone with a temperature of 140° C - 220° C. Theilite-smectite-chlorite and sericite zone was located at the depth of ± 454- ± 533 mcharacterized by the presence of illit-smectite, chlorite, sericite, calcite and quartz minerals. Thiszone, according to the alteration zone division, was comprised of argillic zone with a temperatureof 200° C - 250° C. It was concluded that the alteration rocks in PNT-1 well were estimated toserve as caprock zone of the Geothermal Panti system which formed due to the interactionbetween rocks and acidic to neutral fluid in temperatures between 140° C - 250° C.